The Route and Purpose of Champlain’s Journey to the Petun in 1616 - Garrad, Charles (Ontario History)

(untitled) (The Ontario Historical Society, 2015)
The route taken by Samuel de Champlain and party in 1616, during which he encountered Cheveux-relevés-Odawa and Petun-Wyandot peoples, and also some visiting Neutrals, is again considered. Previous conclusions are confirmed. That Champlain’s purpose was to proceed to the Neutrals, and possibly further to China, and his reasons for not doing so, are suggested.